PUBLIC DISCLOSURE OF TAX RETURN INFORMATION – EXPERIENCE OF SELECTED COUNTRIES - Gałuszka, Jolanta (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
This paper presents an overview of the issues raised by public disclosure of tax return information by providing current and historical perspectives. The debate over whether tax privacy promotes individual tax compliance is as old as the income tax itself. But debate over the public disclosure in the income tax context resurfaces often, especially when the government seeks innovative ways to address the „tax gap” or the difference between the amount of tax that taxpayers should pay and the amount that they actually pay voluntarily. This article considers dilemmas from the economic and social point of view, as well as the viability of public tax disclosure. The purpose of the article is to analyse fundamental economic and social issues, including advantages and disadvantages of public tax disclosure. The intention of the author is to answer the question, whether the public tax disclosure has a positive effect on the condition of the public finance, by improving tax collection and hence increasing tax revenues? There is little empirical evidence of the impact of public disclosure on tax compliance. Indeed, one academic study – „The effect of public disclosure on reported taxable income: evidence from individuals and corporations in Japan”, by Makoto Hasegawa, Jeffrey L. Hoopes, Ryo Ishida and Joel Slemrod– suggests that there may be a negative correlation. This study of responses to income tax disclosure by Japanese multinationals concluded that both corporate and individual taxpayers perceive disclosure as costly and want to avoid it, but for corporate taxpayers, the disclosure regime does not appear to increase firm’s reported taxable income. Alternatively, it may be more appropriate to address the „transparency” concerns through the company and business reporting standards. The Oxford University Centre for Business Studies recently examined the financial reporting of information country by country in its report Transparency in reporting financial data by multinational corporations. The report states that further research and investigation is necessary before it is possible to conclude on the merits of additional reporting disclosure proposals